2015
DOI: 10.1038/tp.2015.152
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin-13, a risk gene for ADHD and comorbid disorders, impacts GABAergic function in hippocampus and cognition

Abstract: Cadherin-13 (CDH13), a unique glycosylphosphatidylinositol-anchored member of the cadherin family of cell adhesion molecules, has been identified as a risk gene for attention-deficit/hyperactivity disorder (ADHD) and various comorbid neurodevelopmental and psychiatric conditions, including depression, substance abuse, autism spectrum disorder and violent behavior, while the mechanism whereby CDH13 dysfunction influences pathogenesis of neuropsychiatric disorders remains elusive. Here we explored the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
94
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 79 publications
(105 reference statements)
14
94
3
Order By: Relevance
“…Not only does our work complement several lines of evidence converging to hippocampal implication in patients with ADHD (Plessen et al, 2006;Posner et al, 2013Posner et al, , 2014Ho et al, 2015;Rivero et al, 2015), but also it extends these findings with respect to functional connectivity. In line with our asymmetry results, Posner and colleagues (Posner et al, 2014) found reduced volume and functional connectivity in the left hippocampus of ADHD children with respect to controls, and associated these modifications with depressive symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…Not only does our work complement several lines of evidence converging to hippocampal implication in patients with ADHD (Plessen et al, 2006;Posner et al, 2013Posner et al, , 2014Ho et al, 2015;Rivero et al, 2015), but also it extends these findings with respect to functional connectivity. In line with our asymmetry results, Posner and colleagues (Posner et al, 2014) found reduced volume and functional connectivity in the left hippocampus of ADHD children with respect to controls, and associated these modifications with depressive symptoms.…”
Section: Discussionsupporting
confidence: 77%
“…Each of these observations fit with reported modest human CDH13 associations with ADHD, which is more frequently diagnosed in males (40). However, the sizes of these effects are small, as are the modest effects noted by others in some mnemonic parameters of the conditional knockout mice (20). There are also no effects of constitutive changes in CDH13 on trained performance on the 5-choice serial reaction time task; the same result came from conditional CDH13 knockouts (20).…”
Section: Discussionsupporting
confidence: 67%
“…However, the sizes of these effects are small, as are the modest effects noted by others in some mnemonic parameters of the conditional knockout mice (20). There are also no effects of constitutive changes in CDH13 on trained performance on the 5-choice serial reaction time task; the same result came from conditional CDH13 knockouts (20). The impulsivity phenotype assessed by this test (41) is thus not changed with CDH13 deletion.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations